Circulating tumor-associated antigen-specific IFNγ+4-1BB+ CD8+ T cells as peripheral biomarkers of treatment outcomes in patients with pancreatic cancer - Murakami, Hirotomo; Takahama, Shokichi; Akita, Hirofumi; Kobayashi, Shogo; Masuta, Yuji; Nagatsuka, Yuta; Higashiguchi, Masaya; Tomokuni, Akira; Yoshida, Keiichi; Takahashi, Hidenori; Doki, Yuichiro; Eguchi, Hidetoshi; et al. (Frontiers in Immunology, 2024)
CD8+ T cells affect the outcomes of pancreatic ductal adenocarcinoma (PDAC). Using tissue samples at pre-treatment to monitor the immune response is challenging, while blood samples are beneficial in overcoming this limitation. In this study, we measured peripheral antigen-specific CD8+ T cell responses against four different tumor-associated antigens (TAAs) in PDAC using flow cytometry and investigated their relationships with clinical features. We analyzed the optimal timing within the treatment course for effective immune checkpoint inhibition in vitro. We demonstrated that the frequency of TAA-specific IFNγ+4-1BB+ CD8+ T cells was correlated with a fold reduction in CA19-9 before and after neoadjuvant therapy. Moreover, patients with TAA-specific IFNγ+4-1BB+ CD8+ T cells after surgery exhibited a significantly improved disease-free survival. Anti-PD-1 treatment in vitro increased the frequency of TAA-specific IFNγ+4-1BB+ CD8+ T cells before neoadjuvant therapy in patients, suggesting the importance of the timing of anti-PD-1 inhibition during the treatment regimen. Our results indicate that peripheral immunophenotyping, combined with highly sensitive identification of TAA-specific responses in vitro as well as detailed CD8+ T cell subset profiling via ex vivo analysis, may serve as peripheral biomarkers to predict treatment outcomes and therapeutic efficacy of immunotherapy plus neoadjuvant chemotherapy.